2021
DOI: 10.1371/journal.pntd.0009010
|View full text |Cite
|
Sign up to set email alerts
|

Congenital syphilis in Argentina: Experience in a pediatric hospital

Abstract: In spite of being preventable, Congenital syphilis (CS) is still an important, and growing health problem worldwide. Fetal infection can be particularly aggressive, but newborns can be asymptomatic at birth and, if left untreated, develop systemic compromise afterwards with poor prognosis. We analyzed 61 CS diagnosis cases between 1987–2019 presenting at the Buenos Aires Children’ Hospital. The distribution of cases showed a bimodal curve, with a peak in 1992–1993 and in 2014–2017. Median age at diagnosis was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
7
0
3
Order By: Relevance
“…Regarding congenital syphilis diagnosis, Garcia et al also reported 39% of patients with less than fourfold nontreponemal titers and 29% with equal or even lower titers, not helping to reach diagnosis. 18 In our study, none of the suspected cases had RPR fourfold or higher than maternal titers; nevertheless, all patients were treated if maternal treatment was absent or when adequate and associated with an increase in nontreponemal titers. Since IgM does not cross the placenta, the presence of FTA-ABS IgM positive in four patients confirmed the diagnosis.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Regarding congenital syphilis diagnosis, Garcia et al also reported 39% of patients with less than fourfold nontreponemal titers and 29% with equal or even lower titers, not helping to reach diagnosis. 18 In our study, none of the suspected cases had RPR fourfold or higher than maternal titers; nevertheless, all patients were treated if maternal treatment was absent or when adequate and associated with an increase in nontreponemal titers. Since IgM does not cross the placenta, the presence of FTA-ABS IgM positive in four patients confirmed the diagnosis.…”
Section: Discussionmentioning
confidence: 54%
“…2,10,21 In our study, none of the patients had symptoms, which could be explained by the high percentage of adequately treated mothers without fourfold titer decrease after treatment (55%) and by the small sample size. 4,18,22 An adequate serologic response is defined as a fourfold decline in nontreponemal titers over a period of at least 6 to 12 months of observation. As a result, in pregnant women, the time between treatment and childbirth is typically less than 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These lesions contain a high number of highly contagious treponemas to the touch. It is also very frequent to observe these lesions in congenital syphilis cases, 31 but in our series, this means of transmission was ruled out as all our patients’ mothers presented negative serology to syphilis during pregnancy. The majority of the lesions that infected mothers presented were in the oral mucosa, tongue and hands.…”
Section: Discussionmentioning
confidence: 83%
“…Major challenges that needs to be overcome on a worldwide scale is the issues related to the incorrect treatment of syphilis during pregnancy and the lack of audits to identify aws in the care process and the adequacy of the quali cations of health professionals. A study conducted in Brazil demonstrated these di culties 33 and another one conducted in Argentina pointed out that of the children identi ed with CS and born in hospitals (corresponding to 96% of the total CS cases), only 47% of their mothers completed the antenatal care serological screening, and only four were adequately treated 34 .…”
Section: Neves Et Al (2018)mentioning
confidence: 99%